Main-chain biodegradable liquid crystal derived from cholesteryl derivative end-capped poly(trimethylene carbonate): synthesis and characterisation. Issue 6 (3rd May 2017) - Chen, Guixiang; Yang, Liqun; Liu, Xiaofeng; Xie, Yujiao; Guo, Zhihao; Li, Miao; Guo, Jing; Hu, Jianshe
ABSTRACT: Main-chain biodegradable liquid crystal derived from cholesteryl derivative end-capped poly(trimethylene carbonate) was investigated. The novel liquid crystal was synthesised via ring-opening polymerisation of trimethylene carbonate initiated by cholesteryl derivative with an alkyl spacer and end primary hydroxyl group, without any catalyst. The chemical structure of resulting polymers was verified by 1 H NMR. Liquid crystalline properties were validated by X-ray diffraction, differential scanning calorimetry, and polarising optical microscopy. The results showed that all the synthesised polymers Chol-(CH2 )2 -(TMC)n exhibited mesomorphism in particular temperature ranges because of the introduction of the cholesteryl derivative moiety. Graphical Abstract: